Coherent technologies for flexible optical networks - Ziaie, Somayeh (2020)
Next-generation networks enable a broad range of innovative services with the best delivery by utilizing very dense wired/wireless networks. However, the development of future networks will require several breakthroughs in optical networks such as high-performance optical transceivers to support a very-high capacity optical network as well as optimization of the network concept, ensuring a dramatic reduction of the cost per bit. At the same time, all of the optical network segments (metro, access, long-haul) need new technology options to support high capacity, spectral efficiency and data-rate flexibility. Coherent detection offers an opportunity by providing very high sensitivity and supporting high spectral efficiency. Coherent technology can still be combined with polarization multiplexing. Despite the increased cost and complexity, the migration to dual-polarization coherent transceivers must be considered, as it enables to double the spectral efficiency. These dual-polarization systems require an additional digital signal processing (DSP) subsystem for polarization demultiplexing. This work seeks to provide and characterize cost-effective novel coherent transceivers for the development of new generation practical, flexible and high capacity transceivers for optical metro-access and data center interconnects. In this regard, different polarization demultiplexing (PolDemux) algorithms, as well as adaptive Stokes will be considered. Furthermore, low complexity and modulation format-agnostic DSP techniques based on adaptive Stokes PolDemux for flexible and customizable optical coherent systems will be proposed. On this subject, the performance of the adaptive Stokes algorithm in an ultra-dense wavelength division multiplexing (U-DWDM) system will be experimentally evaluated, in offline and real-time operations over a hybrid optical-wireless link. In addition, the efficiency of this PolDemux algorithm in a flexible optical metro link based on Nyquist pulse shaping U-DWDM system and hybrid optical signals will be assessed. Moreover, it is of great importance to find a transmission technology that enables to apply the Stokes PolDemux for long-haul transmission systems and data center interconnects. In this work, it is also proposed a solution based on the use of digital multi-subcarrier multiplexing, which improve the performance of long-haul optical systems, without increasing substantially, their complexity and cost.